2016
DOI: 10.20882/adicciones.711
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad de predicción del inventario de temperamento y carácter de Cloninger (TCI-R) en la evolución de los trastornos por uso de alcohol.

Abstract: Cloninger's temperament and character inventory is a good instrument to predict the outcome of treatment of patients with alcohol use disorders and the novelty seeking (NS) dimension is strongly related to therapeutic drop-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
1
7
0
1
Order By: Relevance
“…HA was not associated with daily alcohol consumption or the percentage of abstinent days during 6 months of follow‐up in a depressed alcohol‐dependent sample . Three studies reported on the association between HA and treatment retention, with none of those studies showing any significant association.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…HA was not associated with daily alcohol consumption or the percentage of abstinent days during 6 months of follow‐up in a depressed alcohol‐dependent sample . Three studies reported on the association between HA and treatment retention, with none of those studies showing any significant association.…”
Section: Resultsmentioning
confidence: 85%
“…In the only study to report on the association with alcohol consumption , PS was not associated with any difference in alcohol consumption per drinking day or the percentage of days abstinent. PS was not associated with treatment retention in two studies that reported this outcome , while one study reported that persistence scores were significantly higher ( P < 0.05) among treatment completers (T‐score 51.1) compared to dropouts (T‐score 47.9).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Introducción S e ha demostrado una fuerte asociación entre rasgos de personalidad, como la impulsividad y la búsqueda de sensaciones, con el consumo de sustancias (Mitchell y Potenza, 2014) y los trastornos por consumo de sustancias (Anderson, Tapert, Moabad, Crowley, y Brown, 2007;Ávila et al, 2016;Hicks, Durbin, Blonigen, Iacono, y McGue, 2012;Kotov, Gamez, Schmidt, y Watson 2010;Sher, Bartholow, y Wood, 2000). Además, los rasgos de personalidad evaluados durante la adolescencia y la adultez temprana han mostrado ser buenos predictores del inicio en el consumo de drogas y la transición a problemas relacionados con dicho consumo (Cho et al, 2015;Gonzálvez, Espada, Guillén-Riquelme, Secades y Orgilés, 2016;Nees et al, 2012).…”
unclassified